ПРЕФИКСАЛЬНЫЕ ПРИЛАГАТЕЛЬНЫЕ ЦВЕТА В СОВРЕМЕННОЙ РУССКОЙ ПРЕССЕ - НАРЛОХ, АНДЖЕЙ (Studia Rossica Posnaniensia, 2006)
The article presents an attempt at structural and semantic description of colour adjectives with prefixes in Russian. Today new fixed word construction with metaphorical meaning of colour appear in the press. More and more often their semantic meaning is modified by prefixes. At the same time a lot of the colour terms combine with the prefixes of Greek-Latin etymology, like: анти-, apxu-, гипер-, пост-, супер-, ультра-. In the first part of the work all prefixes which combine with basic colour terms have been assigned. Non-basic colour terms don’t combine with the aforementioned prefixes. In the course of analysis the prefixes with meaning of intensification are noticed as most representative.